The Role of the French Language in facilitating Trade: A Case Study of Maje Border Town Markets - Oriakpono, Mabel (NIU Journal of Humanities, 2024)
This study explores the role that the French language plays in promoting trade in Maje's marketplaces, a well-known border town. Maje, which is located where cultural and economic exchanges converge, provides an intriguing backdrop for examining the complex relationships that exist between language, trade, and cross-border connections. The research explores the particular ways in which the French language influences business operations, communication patterns, and market dynamics in Maje through the use of a case study technique enhanced by anthropological inquiry. The study looks at how common French is among dealers, clients, and other stakeholders as a lingua franca through observations, interviews, and linguistic studies. The study looks into the various ways that the French language is used in the marketplace to facilitate cross-cultural interactions, negotiate agreements, and mediate transactions. It examines the linguistic tactics used by market players, such as code-switching, language accommodation, and cultural adaptation, to take capitalize on French proficiency for business benefit. The study also assesses the effects of fluency in French on competitive advantage, market segmentation, and market integration. It takes into account how linguistic asymmetries and impediments may affect a variety of stakeholders' access to markets, ability to establish trust, and economic prospects. Our understanding of the socio-economic dynamics driving cross-border commerce is enhanced by this study's illumination of the complex interactions between language and trade in border town markets. In border regions where the French language is significant, the findings offer insightful information to policymakers, market participants, and language planners who aim to encourage inclusive economic development and cross-cultural understanding. Keywords:   French language, Trade promotion, Linguistic tactics, Market dynamics, Cross-cultural interactions, Competitive advantage